Pengaruh Debt To Equity Ratio Terhadap Return On Asset Pada Perusahaan Asuransi Jiwa Syariah - Sarehan Khwankawin; Yasir Yasir; Aneu Puspita (Syar'Insurance: Jurnal Asuransi Syariah, 2023)
Abstract: As the main goal of a company is to maximize profits, to increase the value of the company which can be measured using the profitability ratio, namely return on assets. In addition, it is also necessary to pay attention to other ratios to measure the soundness of a company to achieve profit targets, one of which is by using a solvency ratio, namely the debt to equity ratio. This study will discuss the effect of the debt to equity ratio on return on assets in sharia life insurance companies in 2017-2021. This study uses a quantitative method using descriptive statistical tests, classical assumption tests, panel data regression tests, hypothesis testing and the coefficient of determination. The data used is secondary data obtained from the official website of a sharia life insurance company in Indonesia. The results showed that the debt to equity ratio had a significant effect on return on assets. Testing the results of the hypothesis found that the value of t count > t table was 5.808281 > 1.69236 with a significance level of 0.0000 <0.05. After statistical analysis, it is known that the regression analysis model equation ROA = 0.044863 + 0.012515 DER + εti. The R^2 value is 0.509483 which means 50%, this means that 50% of the Return on Assets is influenced by the Debt to Equity Ratio and the remaining 50% is influenced by other variables not examined in this study.